Anaphylaxis to the Citrus Fruit Yuzu - Lefèvre S; Jacquenet S; Richard C; Astafieff K; Peru L; Froelicher Y; Kanny G (Global Journal of Allergy - Peertechz Publications, 2015)
Introduction: We report a selective anaphylaxis to yuzu (Citrus junos).  Case Presentation: A 42-year-old woman, with no atopic history, has experienced two anaphylactic reactions after consuming yuzu. Skin prick tests (SPTs) were performed with juice, peel and pulp of commercially available lemon, orange, grapefruit, tangerine and yuzu, 2 cultivars of Citrus junos, 2 cultivars of Citrus reticulata, one Citrus ichangensis and food consumed during the culprit meal. Basophil activation test and immunoblot were also performed. Result: Skin prick test to juice and peel of yuzu and basophil activation test to juice of yuzu were positive. The protein recognized by IgE is a protein of 23 kDa. Conclusion: Our patient presents a selective food allergy to yuzu. She consumed other citrus fruits (lemon, orange, grapefruit, and tangerine) without any reaction.